The Mechanisms Underlying Chronic Inflammation in Rheumatoid Arthritis from the Perspective of the Epigenetic Landscape - Yasuto Araki; Toshihide Mimura (Journal of Immunology Research)
Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease that is characterized by synovial hyperplasia and progressive joint destruction. The activation of RA synovial fibroblasts (SFs), also called fibroblast-like synoviocytes (FLS), contributes significantly to perpetuation of the disease. Genetic and environmental factors have been reported to be involved in the etiology of RA but are insufficient to explain it. In recent years, accumulating results have shown the potential role of epigenetic mechanisms, including histone modifications, DNA methylation, and microRNAs, in the development of RA. Epigenetic mechanisms regulate chromatin state and gene transcription without any change in DNA sequence, resulting in the alteration of phenotypes in several cell types, especially RASFs. Epigenetic changes possibly provide RASFs with an activated phenotype. In this paper, we review the roles of epigenetic mechanisms relevant for the progression of RA.